An international feminist challenge to theory (Advances in gender research)
Introduction: an international feminist challenge to theory / Vasilikie Demos, Marcia Texler Segal -- Women redefining politics: between new challenges and old illusions / Paola Melchiori -- Theory incorporated / Vicki Kirby -- Feminism of color challenges white sociological theory and color-blind eco-feminism / Laura Corradi -- The biomedical digitalization of women's bodies and women's body politics in the context of globalization: challenges to women-and-health research / Annemiek Richters -- The nature/culture dualism in the Indian context / Abha Chauhan -- Postmodern feminism challenges organization theory / Gladys L. Symons -- Much ado about gender: a conceptual travelogue / Barbara L. Marshall -- It's the 21st century - do you know what gender you are? / Judith Lorber -- The devolution of women as a category in development theorizing: is this an essential move? / Iêda Chapoval -- Rethinking development from a feminist perspective / Ann Denis -- Sisters' keepers: economic organizing among informally employed women in Turkey / Simel Esim -- In search of the good life: feminist correctives to modernization theory / Janet Zollinger Giele -- Feminist nebula: theoretical approaches on representations of feminism in Recife / Lady Selma Ferreira Albernaz -- Being a white Australian-Canadian feminist doing research with South Asian women of color in the diaspora: crossing borders and boundaries, creating spaces / Helen Ralston -- Can research, activism, and feminism converge? some notes on collaborative action-oriented inquiry / Deborah Harrison